2014
DOI: 10.1111/jasp.12252
|View full text |Cite
|
Sign up to set email alerts
|

How does stigma spoil relationships? Evidence that perceived discrimination harms romantic relationship quality through impaired self‐image

Abstract: Research is beginning to reveal negative effects of perceived discrimination on romantic relationship quality among members of devalued groups, yet potential mechanisms driving these effects remain underexplored. In the current work, we examined the mediating role of self-image. Data from two cross-sectional studies with samples composed of racial minorities (Study 1) and sexual minorities (Study 2) provided support for a model, whereby the negative association between perceived discrimination and romantic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 62 publications
(88 reference statements)
2
55
0
Order By: Relevance
“…In line with past research (e.g., Doyle & Molix, 2013;Murry et al, 2001;Trail et al, 2012), we found that social stigma salience consistently evidenced a negative effect on self-reported romantic relationship quality for individuals involved in shorter relationships. In other words, experiences with prejudice and discrimination, including acute experiences, can harm the romantic relationships of members of devalued groups.…”
Section: Discussionsupporting
confidence: 86%
“…In line with past research (e.g., Doyle & Molix, 2013;Murry et al, 2001;Trail et al, 2012), we found that social stigma salience consistently evidenced a negative effect on self-reported romantic relationship quality for individuals involved in shorter relationships. In other words, experiences with prejudice and discrimination, including acute experiences, can harm the romantic relationships of members of devalued groups.…”
Section: Discussionsupporting
confidence: 86%
“…In a study using a community sample of LGB individuals, Frost and Meyer (2009) reported that depressive symptoms-hypothesized to result from internalized homonegativity-seem to be the mechanism behind their participants' relationship problems. Szymanski and Hilton (2013) suggested that internalized homonegativity might generate fear of intimacy and thus negatively affect relationship quality in male same-sex couples, while Doyle and Molix (2014a) showed that a negative association between perceived discrimination and same-sex relationship quality is partially mediated by impaired self-image. Finally, in a study of coupled gay men, Kamen et al (2011) found the associations between minority stressors and relationship satisfaction moderated by specific relationship characteristics.…”
Section: Intimacy Romantic Relationships and Minority Stressmentioning
confidence: 97%
“…Considering the volume of studies discussing the role of discrimination and stigma in LGB persons' lives on the individual level, including the confirmed mental health disparities between LGBs and heterosexuals (Fergusson, Horwood, Ridder, & Beautrais, 2005;Lewis, 2009;Logie, 2012;Sandfort, de Graaf, Bijl, & Schnabel, 2001), it is surprising that only a few studies so far have investigated the role of minority stressors in same-sex couple functioning (see Doyle & Molix, 2014a;Frost, 2011;Frost & Meyer, 2009;Kamen, Burns, & Beach, 2011;Mohr & Daly, 2008;Otis, Rostosky, Riggle, & Hamrin, 2006;Szymanski & Hilton, 2013). Using the personal projects analysis method, Frost (2011) found that LGB participants reported significantly more devaluation and barriers (via prejudice, discrimination, and stigmatization) to the development of intimacy in their relationships than did heterosexual individuals.…”
Section: Intimacy Romantic Relationships and Minority Stressmentioning
confidence: 97%
“…Couples who do not have social support are at risk for lowered individual self-esteem and relationship satisfaction (Doyle & Molix, 2014), and heightened domestic violence (Balsam & Szymanski, 2005). While some couples attempt to deter these negative outcomes by concealing their relationship, concealment exasperates negative consequences, and leads to reduced commitment, increased substance use, risk taking behaviors, and negative somatic symptoms relating to stress (Lehmiller, 2009(Lehmiller, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Doyle and Molix (2014) showed that individuals in stigmatized relationships reported an impaired self-image, which perpetuated the relational strain with significant or intimate others. Balsam and Szymanski (2005) found that minority stress and lack of social support in lesbian relationships led to lower relationship quality and an increase in domestic violence between the partners.…”
mentioning
confidence: 99%